Pemanfaatan Media Pembelajaran Berbasis Powerpoint Terhadap Minat Belajar Siswa Pada Mata Pelajaran Informatika Di Kelas X DKV 3 SMK Negeri 1 Bengkulu Selatan - Sani, Lorna Fitri; Sembiring, Lina Tri Astuti Br; Hermawansya, Hermawansya (LPPJPHKI Universitas Dehasen Bengkulu, 2024)
This study aims to determine the utilization of powerpoint-based learning media on students’ learning interest in Informatics subject in class X DKV 3 SMK Negeri 1 of South Bengkulu. The method used in this research is a qualitative research method with a type of descriptive research with a qualitative approach. Data collection techniques in the form of questionnaires, observation, and documentation, the subjects of this study were 34 students of class X DKV 3 SMK Negeri 1 of South Bengkulu in Informatics subject. The results of this study based on the results of questionnaires, observations and documentation conducted that the utilization of powerpoint-based learning media has a positive impact in learning Informatics subject in class X students. Teachers who are able to use this media are able to manage the class better and pay attention to students who are not focused when watching learning videos. The results of the student learning interest response questionnaire are on the indicator of feelings of pleasure 68%. Interest indicator is 64%, student attention indicator is 81%, and student involvement/participation indicator is 63%. It is concluded that the results of the use of powerpoint-based learning media on the material of the social impact of informatics can be categorized as good because it can foster interest in learning and enthusiasm for students in following the learning process.